2020
DOI: 10.1186/s12883-020-01805-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of generalization of ocular myasthenia gravis under immunosuppressive therapy in Northwest China

Abstract: Background It is well demonstrated that immunosuppressants can reduce, but not eliminate the risk of generalized development in ocular myasthenia gravis (OMG). In this study, we aimed to explore the predictive factors of generalized conversion of OMG patients who received immunosuppressive treatments. Methods OMG patients under immunosuppressive treatments in Tangdu Hospital from June 2008 to June 2012 were retrospectively reviewed. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 27 publications
7
26
0
Order By: Relevance
“…Several previous studies have found that decreased responses were more frequent in patients who experienced conversion to generalized MG than in those who remained ocular. 8 10 14 However, several points should be considered when interpreting these data, especially regarding the results of the RNS test. In one study, the results were not statistically significant after adjusting for other variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies have found that decreased responses were more frequent in patients who experienced conversion to generalized MG than in those who remained ocular. 8 10 14 However, several points should be considered when interpreting these data, especially regarding the results of the RNS test. In one study, the results were not statistically significant after adjusting for other variables.…”
Section: Discussionmentioning
confidence: 99%
“… 10 A recent study that showed that a positive RNS test for the facial muscle was an independent predictor only analyzed subjects with ocular MG under immunosuppressive therapy. 14 In addition, the RNS test was conducted mainly on the facial nerve, and applied to the ulnar nerve in only 34% of the patients. Since the RNS test was not conducted in every patient in a consistent manner, the possibility of selection bias exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it may be used to monitor treatment response. RNS abnormality in a peripheral muscle in ocular onset MG increases the risk of generalization, according to some authors [62,63]. In an emergency setting, RNS may distinguish a cholinergic crisis from a myasthenic crisis [48].…”
Section: Repetitive Nerve Stimulationmentioning
confidence: 99%
“…The factors which are proposed to be associated with generalization are older age at onset, RNS abnormalities in facial nerve, AChR antibody positivity, less use of early immunosuppressive therapy, presence of thymoma, and shorter disease duration. [97][98][99][100] However, these studies were retrospective and the patients were treated with immunosuppressive agents, which might have confounded the association results due to their disease modifying effects. 74 Though a study to evaluate the risk factors in nonimmunosuppressed patients is required; it might not be ethically justified.…”
Section: Progression To Generalized Myasthenia Gravismentioning
confidence: 99%